The antecedents and consequences of organizational learning in the library: A systematic literature review - Srirahayu, Dyah Puspitasari; Eliyana, Anis; Anugrah, Esti Putri (SAGE Publications Ltd, 2022)
The aim of this study is to determine the developments and factors that affect organizational learning in libraries. The study uses a systematic literature review method by analysing 20 research articles. The results of the study indicate that there are antecedents and consequences of organizational learning in the library. The research offers a comprehensive framework of the antecedents and consequences of organizational learning in libraries. Library managers can use these results to improve organizational learning in their libraries in accordance with the conditions and environment. The results can also be used as material for consideration in making decisions about the application of organizational learning in the library. There are few systematic literature reviews of organizational learning in libraries; hence, this article can be used as an opening for further discussion.